CLIMATE RISK AUDITING IN PUBLIC SECTOR FINANCE: A NEW PARADIGM FOR ACCOUNTABILITY - Theresia Febiengry Sitanala; Adonia Anita Batkunde (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Climate change has become a systemic risk with a significant impact on the financial stability of the public sector, necessitating a new approach to audit practice to ensure more comprehensive accountability. This study aims to examine the concept of climate risk auditing as a new paradigm in public sector financial auditing using a literature review method. The study analyzes various scientific sources, international institutional reports, and relevant regulations to identify developments, challenges, and implications for implementing climate risk audits. The results indicate that integrating climate risk into the audit process not only broadens the scope of traditional audits but also encourages increased transparency, disclosure of non-financial risks, and strengthened public sector governance. Furthermore, auditors are required to possess new competencies that include an understanding of sustainability issues, environmental risk analysis, and the use of technology-based data. This study also found that there are still limitations in audit standards that specifically address climate risk, necessitating the development of an audit framework that is adaptive and responsive to the dynamics of climate change. Thus, climate risk auditing is a crucial element in strengthening public accountability and supporting sustainable decision-making in the public sector.